Exposome changes in primary school children following the wide population non-pharmacological interventions implemented due to COVID-19 in Cyprus: A national survey. (February 2021) - Konstantinou, Corina; Andrianou, Xanthi D.; Constantinou, Andria; Perikkou, Anastasia; Markidou, Eliza; Christophi, Costas A.; Makris, Konstantinos C.
Abstract: Background: Non-pharmacological interventions (NPI), including lockdowns, have been used to address the COVID-19 pandemic. We describe changes in the environment and lifestyle of school children in Cyprus before the lockdown and during school re-opening, and assess compliance to NPI, using the exposome concept. Methods: During June 2020, parents completed an online questionnaire about their children's lifestyle/behaviours for two periods; school re-opening (May 21-June 26) following the population-wide lockdown, and the school period before lockdown (before March). Findings: Responses were received for 1509 children from over 180 primary schools. More than 72% of children complied with most NPI measures; however, only 48% decreased the number of vulnerable contacts at home. Sugary food consumption was higher in the post-lockdown period with 37% and 26% of the children eating sugary items daily and 4–6 times/week, compared to 33% and 19%, respectively, for the pre-lockdown period ( p <0.001). Children's physical activity decreased compared to pre-lockdown ( p <0.001), while screen time increased in the post-lockdown period, with 25% of children spending 4-7 hours/day in front of screens vs. 10% in the pre-lockdown period ( p <0.001). About half of the children washed their hands with soap 4–7 times/day post-lockdown vs. 30% in the pre-lockdown period ( p <0.001). Interpretation: This national survey showed a high degree of compliance to NPI measures among school children. Furthermore, the exposome profile of children may be affected in the months following NPI measures due to alterations in diet, physical activity, sedentary behaviour, and hand hygiene habits. Funding: Partial funding by the EXPOSOGAS project, H2020 Research and Innovation Programme (grant #810995).